1987
DOI: 10.1143/jjap.26.1463
|View full text |Cite
|
Sign up to set email alerts
|

A Vortex Transitional NDRO Josephson Memory Cell

Abstract: A new vortex transitional NDRO memory cell has been proposed for use as a high-speed cache memory. The memory cell consists of two superconducting loops with one Josephson junction and a two-junction interferometer gate. The superconducting loop stores single-flux quantum. The interferometer gate operates as a sense gate. The memory cell employs a vortex transition in the superconducting loop for the writing and reading of data. The sense gate current margin increases to ±38% since the coupling magnetic flux i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…6 mark amplitudes of the IX and IY currents at successful operation cycles of the tested cells, while green crosses mark incorrect operation. The measured margins are similar to the ones projected in [5], demonstrating that performance of the fabricated circuits is in a good agreement with the theoretical model. We attribute wider margins of the VT2 cells in comparison to the ones observed on VT1 cells to a better layout optimization and parameter extraction, mainly to a better account for the mutual inductances between all the cell inductors, including parasitics -the experience gained as a result of our work on the VT1 cells.…”
Section: Circuit Design and Test Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…6 mark amplitudes of the IX and IY currents at successful operation cycles of the tested cells, while green crosses mark incorrect operation. The measured margins are similar to the ones projected in [5], demonstrating that performance of the fabricated circuits is in a good agreement with the theoretical model. We attribute wider margins of the VT2 cells in comparison to the ones observed on VT1 cells to a better layout optimization and parameter extraction, mainly to a better account for the mutual inductances between all the cell inductors, including parasitics -the experience gained as a result of our work on the VT1 cells.…”
Section: Circuit Design and Test Resultssupporting
confidence: 80%
“…Unfortunately, it has not been complemented by a similar revolution in JJ-based random access memories (RAM). The development of superconductor RAMs slowed down after the demonstration of a Vortex Transitional (VT) memory cell [5], [6] and VT-based RAM circuits in 1990s [7], [8]. The 4-Kbit level of RAM integration achieved at that time was in line with available fabrication technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CMOS design, it is common to use the RAM-based cache. Although, in SFQ design, there are some RAM-based memory technologies such as Vortex Transition Cell (or VTC) [35], they are not fast enough to provide data to microprocessors which operate over 100 GHz. Therefore, shift-register-based memory technology is employed to achieve more fast access speed.…”
Section: Bit-parallel Sfq Cache Architecturementioning
confidence: 99%
“…Vortex-based memory has also shown promising results in terms of its scalability. Tahara et al [19] demonstrated vortex-based NDRO in one of the earliest accounts of this memory. Numata et al [20] demonstrated a high-density memory application with a relatively lower area.…”
Section: Introductionmentioning
confidence: 98%